2006
DOI: 10.1063/1.2266571
|View full text |Cite
|
Sign up to set email alerts
|

Organic oxide/Al composite cathode in small molecular organic light-emitting diodes

Abstract: This study addresses the feasibility of using an organic oxide/Al composite cathode to fabricate the small molecular organic light-emitting diodes (OLEDs). A supplementary organic buffer film is placed at the interface between the tris(8-hydroxyquinoline) aluminum (Alq3) and the organic oxide/Al complex layers. Incorporating the rubrene/poly(ethylene glycol) dimethyl ether (PEGDE) buffer layers into the composite cathode structure markedly improves the performance of devices. The luminous efficiencies of Alq3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The above result probably implies that the ethylene oxide‐based thin film could work well as a buffer with Al electrodes, although the improvement on the V OC and η for P3HT:PCBM‐based OPVs made of PEO as the electrode buffer in Oh et al’s report was limited. Nevertheless, PEO‐based polymers and molecules have been successfully reported as effective electrode buffers with Al cathodes for the fabrication of high performance organic/polymer light‐emitting diodes (O/PLEDs) 30, 33–36. We attribute the debate as resulting from the different processing conditions when utilizing the PEO polymer as the electrode buffer, because it tends to absorb the moisture in the atmosphere, to crystallize, to change the thin film morphology, and – most importantly – is intrinsically an insulating polymer material.…”
Section: Introductionmentioning
confidence: 99%
“…The above result probably implies that the ethylene oxide‐based thin film could work well as a buffer with Al electrodes, although the improvement on the V OC and η for P3HT:PCBM‐based OPVs made of PEO as the electrode buffer in Oh et al’s report was limited. Nevertheless, PEO‐based polymers and molecules have been successfully reported as effective electrode buffers with Al cathodes for the fabrication of high performance organic/polymer light‐emitting diodes (O/PLEDs) 30, 33–36. We attribute the debate as resulting from the different processing conditions when utilizing the PEO polymer as the electrode buffer, because it tends to absorb the moisture in the atmosphere, to crystallize, to change the thin film morphology, and – most importantly – is intrinsically an insulating polymer material.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports indicated that device performance can be improved substantially by placing a thin layer of polymer oxide ͑surfactant͒, such as poly͑ethylene glycol͒ ͑PEG͒, on the cathode interface, [12][13][14] or by blending such materials into the active layer of devices. 15,16 This enhanced device performance is attributed to the chemical interaction between PEG and the Al cathode decreasing the electron injection barrier and contact resistance.…”
mentioning
confidence: 99%
“…15,16 This enhanced device performance is attributed to the chemical interaction between PEG and the Al cathode decreasing the electron injection barrier and contact resistance. [12][13][14][15][16] In this study, we applied this method to achieve efficient phosphorescent PLEDs. We obtained lower operating voltages and higher power efficiencies after blending PEG into the electroluminescent ͑EL͒ layer.…”
mentioning
confidence: 99%
“…Guo et al reported that high performance polymer and small molecule OLEDs with an organic oxide, poly(ethylene glycol) dimethyl ether (PEGDE). Because PEGDE can be evaporated at low temperature compared to other inorganic insulators and improves the device performance as much as the inorganic electron injection layers, it could be a good candidate for an organic electron injection layer [15][16][17]. In this study, the performance of PVK based PLEDs is improved by using PEO/Ca/Al cathode.…”
mentioning
confidence: 83%